Hypercoagulation syndrome at liver cirrhosis - I. A. Kurkina; M. V. Mayevskaya; B. V. Silayev; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present modern data on hypercoagulation syndrome at liver cirrhosis.Key points. Changes in hemostasis system at liver cirrhosis have complex and ambiguous character. The total effect of all changes is frequently balanced, and the hemostatic system remains functional. However hemostasis equilibrium at liver cirrhosis is unstable. There is always potential risk of both hemorrhage and thromboses. As the possible reasons causing clotting, decrease of plasma anticoagulants level, elevation of von Willebrand factor level, decrease of ADAMTS13 protease level, changes of vascular wall and decrease of profibrinolytic factors level are taken into account. Application of anticoagulants for liver cirrhosis patients becomes an actual issue nowadays.Conclusion. Patients with liver cirrhosis are distinguished by high risk of both hemorrhagic, and thrombotic complications, that requires profound investigation of hemostasis system. Prescription of anticoagulant therapy to such patients should be based on verified thrombosis, absence of direct contra-indications, considering risk of anticoagulant therapy complications.